Experimental investigation of laminar flow and heat transfer characteristics in square minichannels with twisted tapes. (September 2020) - Feng, Zhenfei; Ai, Xin; Wu, Peilin; Lin, Qingyu; Huang, Zuqiang
Highlights: Laminar flow and heat transfer in minichannels with twisted tapes are studied. Effects of twisted tape length and twist ratio on performance are investigated. Twisted tape improves overall thermal performance in a minichannel heat sink. Empirical correlations for heat transfer coefficient and pressure drop are developed. Abstract: The flow and heat transfer characteristics of distilled water in a minichannel heat sink (MCHS) fitted with twisted tapes under laminar flow are investigated experimentally in present study. Nine twisted tapes with lengths of L t = 50 mm, 100 mm and 150 mm, and twist ratios of Y = 3, 4, and 5 are employed as inserts. The results show that average heat transfer coefficient ( h ave ), pressure drop per unit length (Δ P pul ) and thermal enhancement factor ( η ) increase with the decrease in twist ratio or/and the increase in twisted tape length. The heat transfer enhancement factor ( h ave / h ave, 0, where subscript 0 denotes plain MCHS) and the pressure drop increasing factor (Δ P pul /Δ P pul, 0 ) are in the ranges of 1.29–2.49 and 1.68–4.72, respectively. The average values of η for each MCHS with twisted tape are in a range of 1.09–1.46. The full-length ( L t = 150 mm ) twisted tape with Y = 3 yields the best heat transfer rate, the highest flow resistance and the best overall thermal performance compared to other eight twisted tapes. In addition, the empirical correlations for h ave and Δ P pul are developed based on the experimental results. The predicted h ave and Δ P pul are within ±5% and ±6% deviation, respectively, compared to the experimental data.